ANALISIS NARASI / DISKURSUS TERHADAP KEBIJAKAN PERHUTANAN SOSIAL Di WILAYAH KERJA PERHUTANI - Ramli Ramadhan; Risna Noviati Amalia (Wahana Forestra: Jurnal Kehutanan, 2021)
The Social Forestry Policy (PS) in the Perhutani working area has started a new beginning towards the current PS implementation. The issuance of regulation P.39 / 2017 was colored by various narratives / discourses from various actors decorating the journey of the policy issuance above. Using a narrative / discourse analysis approach, this study intends to explore the narratives used by parties in the policy process and those who receive the impact of SF policies. The research method used is descriptive qualitative analysis within-depth interviews with selected respondents proportionally (purposive sampling). The results of the study explain that the narrative of each party is different. The narrative brought by the pro to the policy is based on the condition of the forest and the social conditions of the community around the forest that have not been successfully improved, including the PHBM program that needs to be evaluated. The IPHPS scheme provides opportunities for access and higher profit sharing for the community to manage forests with low cover conditions (10%) and or social conditions that need to be addressed. Perhutani brought a narrative about the current regulation violating the previous regulation.